Pengembangan Sistem Informasi Rehabilitasi Korban Penyalahgunaan Napza Pada Kantor BRSKPN SATRIA - Okta Verina Tri Utami; Citra Wiguna; Dwi Mustika Kusumawardani (Journal of Innovation Information Technology and Application (JINITA), 2021)
The Satria Agency for Social Rehabilitation of Drug Abuse Victims (BRSKPN) is a Technical Implementation Unit of the Ministry of Social Affairs of the Republic of Indonesia, which has the task of carrying out social rehabilitation for victims of drug abuse, and focuses on helping improve social roles and functions, as well as recovery of victims of drug abuse. The business processes carried out by the management of the Satria BRSKPN Office consist of viewing, editing, printing service data, administrative data, assessment data, WHOQOL data and others. There were problems that occurred in the rehabilitation process at the Satria BRSKPN Office, including the use of manual forms on paper sheets for the process of managing and documenting rehabilitation data. In this case, a rehabilitation information system is needed to improve rehabilitation services. The purpose of this research is to produce an information system for the rehabilitation of drug abuse victims. The information system is designed using the waterfall method. The waterfall method has the requirements definition stages, system and software design, implementation and unit testing, integration and system testing, and operation and maintenance. The results showed that the rehabilitation information system could be implemented in the BRSKPN Satria Office with the waterfall method that had been tested through the operation and maintenance stages. The rehabilitation information system was able to improve the management and distribution of information in order to facilitate the decision-making process at the Satria BRSKPN Office rehabilitation services.